(untitled) (INTERNATIONAL SCIENTIFIC INNOVATION RESEARCH CONFERENCE, 2025)
This article explores the effectiveness of pair and group work as instructional strategies for enhancing students’ communication skills in English as a Foreign Language (EFL) classrooms. The study aims to investigate how collaborative learning activities influence students’ speaking fluency, interaction, and confidence. A mixed-methods approach was employed, including classroom observations, speaking assessments, and student questionnaires.